Cholecalciferol Supplementation Does Not Prevent the Development of Metabolic Syndrome or Enhance the Beneficial Effects of Omega-3 Fatty Acids in Obese Mice. Issue 5 (13th April 2021) - Valle, Marion; Mitchell, Patricia L; Pilon, Geneviève; St-Pierre, Philippe; Varin, Thibault; Richard, Denis; Vohl, Marie-Claude; Jacques, Hélène; Delvin, Edgar; Levy, Emile; Gagnon, Claudia; Bazinet, Laurent; et al.
ABSTRACT: Background: Cholecalciferol (D3 ) may improve inflammation, and thus provide protection from cardiometabolic diseases (CMD), although controversy remains. Omega-3 fatty acids (ω-3FA) may also prevent the development of CMD, but the combined effects of ω-3FA and D3 are not fully understood. Objectives: We determined the chronic independent and combined effects of D3 and ω-3FA on body weight, glucose homeostasis, and markers of inflammation in obese mice. Methods: We gave 8-week-old male C57BL/6J mice, which had been fed a high-fat, high-sucrose (HF) diet (65.5% kcal fat, 19.8% kcal carbohydrate, and 14% kcal protein) for 12 weeks, either a standard D3 dose (+SD3 ; 1400 IU D3 /kg diet) or a high D3 dose (+HD3 ; 15, 000 IU D3 /kg diet). We fed 1 +SD3 group and 1 +HD3 group with 4.36% (w/w) fish oil (+ω-3FA; 44% eicosapentaenoic acid, 25% docosahexaenoic acid), and fed the other 2 groups with corn oil [+omega-6 fatty acids (ω-6FA)]. A fifth group was fed a low-fat (LF; 15.5% kcal) diet. LF and HF+ω-6+SD3 differences were tested by a Student's t -test and HF treatment differences were tested by a 2-way ANOVA. Results: D3 supplementation in the +HD3 groups did not significantly increase plasma total 25-hydroxyvitamin D and 25-hydroxyvitamin D3 [25(OH)D3 ] versus the +SD3 groups, but it increased 3-epi-25-hydroxyvitamin D3 levels by 3.4 ng/mL in the HF+ω-6+HD3 group and 4.0 ng/mL in the HF+ω-3+HD3 group, representing 30% and 70%, respectively, of the total 25(OH)D3 increase. Energy expenditure increased in those mice fed diets +ω-3FA, by 3.9% in the HF+ω-3+SD3 group and 7.4% in the HF+ω-3+HD3 group, but it did not translate into lower body weight. The glucose tolerance curves of the HF+ω-3+SD3 and HF+ω-3+HD3 groups were improved by 11% and 17%, respectively, as compared to the respective +ω-6FA groups. D3 supplementation, within the ω-3FA groups, altered the gut microbiota by increasing the abundance of S24–7 and Lachnospiraceae taxa compared to the standard dose, while within the ω-6FA groups, D3 supplementation did not modulate specific taxa. Conclusions: Overall, D3 supplementation does not prevent CMD or enhance the beneficial effects of ω-3FA in vitamin D–sufficient obese mice.